University Leadership Based in the Humanities: An Interview with Prof. Hanne Leth Andersen - Hanne Leth Andersen (Ali Khorsandi Taskoh, 2022)
Interview with Prof. Hanne Leth Andersen Rector at Roskilde University, DENMARK